2010
DOI: 10.1001/archinternmed.2009.518
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular Tachycardia After Ingestion of Ayurveda Herbal Antidiarrheal Medication Containing Aconitum

Abstract: Ayurveda is an East Indian tradition involving the treatment of medical ailments through the use of herbal medications. A previously asymptomatic 62-year-old man with a history of hypertension and stable coronary artery disease developed paresthesias and fascicular and ventricular tachycardia after ingestion of an Ayurveda bowel regimen containing substrates from the Aconitum species, which is a known neurotoxin and cardiotoxin. Findings of electrophysiologic study and cardiac magnetic resonance imaging were w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Poisoning due to homemade medicated liquor containing aconite and traditional medicine containing A. carmichaeli were reported in China between 1999 and 2008 (Liu et al, 2011). Severe cases of cardiac toxicity from consumption of aconitine-containing herbal preparation manifesting as ventricular tachycardia and fibrillation and eventually leading to death have been reported (Tai et al, 1992; Fujita et al, 2007; Dhesi et al, 2010; Lin et al, 2011). In other studies bradycardia and hypotension were observed (Chan, 2009).…”
Section: Toxicity and Adverse Health Effects Of Some Common Herbal Mementioning
confidence: 99%
“…Poisoning due to homemade medicated liquor containing aconite and traditional medicine containing A. carmichaeli were reported in China between 1999 and 2008 (Liu et al, 2011). Severe cases of cardiac toxicity from consumption of aconitine-containing herbal preparation manifesting as ventricular tachycardia and fibrillation and eventually leading to death have been reported (Tai et al, 1992; Fujita et al, 2007; Dhesi et al, 2010; Lin et al, 2011). In other studies bradycardia and hypotension were observed (Chan, 2009).…”
Section: Toxicity and Adverse Health Effects Of Some Common Herbal Mementioning
confidence: 99%
“…The use of aconite root for medicinal purposes is common in the Hmong, Asian, and Indian populations to treat various ailments, including heartburn and headache 1 . Raw aconite roots are extremely toxic and must be processed to reduce the alkaloid content before use.…”
Section: Discussionmentioning
confidence: 99%
“…Aconitine binds with high affinity to the voltage-sensitive sodium channel in its open state and suppresses the conformational change to the inactive state, 4 delaying repolarization by prolonging sodium influx and membrane depolarization. Conformational changes to the channel induced by aconitine binding shift the activation threshold of the channel to a more negative potential, 2 while the inactivation curve is shifted toward a more positive potential, resulting in prolonged opening of the channel that predisposes to the development and persistence of triggered activity 1 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In traditional Chinese medicine (TCM) practices, aconitine has been effectively used to treat various ailments despite their toxic effects. Such effects were related to that causing ventricular tachycardia [25], bradycardia, and hypotension [26]. …”
Section: Introductionmentioning
confidence: 99%